2021
DOI: 10.3389/fenrg.2021.717975
|View full text |Cite
|
Sign up to set email alerts
|

The Social Acceptance Factors for Insulation Boards Produced With CO2-Derived Foam

Abstract: The negative consequence of increased greenhouse gas emissions have incited research to focus on developing sustainable technologies to reduce the use of fossil raw material. Carbon Capture and Utilization is such a technology. It reuses captured CO2 as raw material for the production of salable products. Beyond their technical and economic feasibility, the acceptance of these products is vital for the successful roll-out of the technology. The two-step empirical study—a qualitative preliminary study (n = 8 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…With higher subjective knowledge, the intention to fly with CO 2 -based aviation fuels was also higher (H3.2b supported, the other hypotheses for RQ3 were rejected). Interest and knowledge are known to positively influence the acceptance and adoption of sustainable technologies (Simons et al, 2021a). However, the low level of knowledge about CO 2based aviation fuels in the sample indicates a) that this topic is too little present in the public and b) the need for carefully planned information and communication about CO 2 -based aviation fuels by research and airlines.…”
Section: What Drives Social Readiness Of Co 2based Aviation Fuels?mentioning
confidence: 90%
“…With higher subjective knowledge, the intention to fly with CO 2 -based aviation fuels was also higher (H3.2b supported, the other hypotheses for RQ3 were rejected). Interest and knowledge are known to positively influence the acceptance and adoption of sustainable technologies (Simons et al, 2021a). However, the low level of knowledge about CO 2based aviation fuels in the sample indicates a) that this topic is too little present in the public and b) the need for carefully planned information and communication about CO 2 -based aviation fuels by research and airlines.…”
Section: What Drives Social Readiness Of Co 2based Aviation Fuels?mentioning
confidence: 90%
“…Besides an active acceptance or rejection of a technology, individuals can also adopt an indifferent position, where no attitude has been developed yet (Arning et al, 2019). Furthermore, it was shown that social acceptance reactions towards CO 2 -based products are not only relevant when it comes to marketable end products (Arning et al, 2021;Simons et al, 2021b), but the production process was also impacted by acceptance factors (Camacho-Otero et al, 2019;Evans, 2019;Simons et al, 2021a). Apparently, consumers do not only consider the final product but try to gauge the way it is produced.…”
Section: Public Perception and Acceptance In The Context Of Renewable...mentioning
confidence: 99%